Mechanism of Different Stereoisomeric Astaxanthin in Resistance to Oxidative Stress in Caenorhabditis elegans. Issue 9 (16th August 2016) - Liu, Xiaojuan; Luo, Qingxin; Cao, Yong; Goulette, Timothy; Liu, Xin; Xiao, Hang
Abstract: As a potent antioxidant in human diet, astaxanthin (AST) may play important roles in alleviating oxidative stress‐driven adverse physiological effects. This study examined the effects of different stereoisomers of AST in protecting Caenorhabditis elegans from chemically induced oxidative stress. Three stereoisomers of AST investigated herein included 3S, 3´S ( S ) AST, 3R, 3´R ( R ) AST, and a statistical mixture ( S : meso : R = 1:2:1) (M ) AST. Under paraquat‐induced oxidative conditions, all three types of AST significantly enhanced survival rate of C. elegans . The accumulation levels of ROS in the worms were reduced by 40.12%, 30.05%, and 22.04% by S, R, and M AST, respectively ( P < 0.05). Compared with R and M AST, S significantly enhanced the expression levels of SOD‐3. The results of RNA‐Seq analysis demonstrated that AST protected C. elegans from oxidative damage potentially by modulating genes involved in the insulin/insulin‐like growth factor (IGF) signaling (IIS) pathway and the oxidoreductase system. It is noteworthy that different stereoisomers of AST showed different effects on the expression levels of various genes related with oxidative stress. This study revealed important information on the in vivo antioxidative effects of AST stereoisomers, which might provide useful information for better utilization of AST.